1997
DOI: 10.1159/000185442
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and 6-Hydroxymelatonin Sulfate Excretion Is Inversely Correlated with Gonadal Development in Children

Abstract: To delineate the development of melatonin (MLT) production during childhood, we measured the excretion of MLT and 6-hydroxymelatonin sulfate (MLTS) in the urine of children (n = 134) from the 26th week of gestation until the age of 20 years. MLTS excretion showed a diphasic pattern with declining values in preterm babies with lowest values around term. After birth, the values remained low for the first 6 months of life. The highest values were reached between 4 and 7 years of age with a smooth but steady decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
(24 reference statements)
0
13
1
Order By: Relevance
“…A strong inverse correlation has been documented between the nocturnal concentration of melatonin and age, Tanner stage and the LH concentration [39, 40]. Nevertheless, in our cases with morning samples, no correlation was found in the overall group (with two evaluations for every subject) between melatonin and LH, in either sex.…”
Section: Discussioncontrasting
confidence: 50%
“…A strong inverse correlation has been documented between the nocturnal concentration of melatonin and age, Tanner stage and the LH concentration [39, 40]. Nevertheless, in our cases with morning samples, no correlation was found in the overall group (with two evaluations for every subject) between melatonin and LH, in either sex.…”
Section: Discussioncontrasting
confidence: 50%
“…[5] By 6-8 years, the levels are similar to adult levels; however, MLT expression decreases once again between 8-13 years of age, and increases again between 13-15 years of age. MLT receptor expression has been verifi ed in many tissues and organs, and studies [2,6] have demonstrated the various biological effects of MLT: day-night rhythm regulation, sexual maturation, reproduction, immune reaction, tumor and aging, modulation of arterial blood pressure and heart rate, free radical clearance and antioxidation, as well as inhibition of platelet aggregation and lipid peroxidation.…”
Section: Original Articlementioning
confidence: 85%
“…[5] In addition, lymphocyte phenotype and function are different between adults and children. In this study MLT enhanced the proliferation of neonatal mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…6-OHMS is the major enzymatic metabolite of melatonin [48] and has frequently been shown to correlate with serum melatonin concentrations [34,35]. The well-documented rapid fall of melatonin levels in serum from childhood to puberty [47] is mainly correlated with an increase in body mass during that period with a corresponding increase in serum volume rather than a decreasing melatonin production, analyzed here with 24-hour urine samples.…”
Section: Discussionmentioning
confidence: 99%